Effect of Row Spacing on The Productivity of Anjan Grass (CENCHRUS Ciliaris) With Caribbean Stylo Under Different Levels of Phosphorus - Rai, P (Annals of Arid Zone, 2016)
Studies on three row spacing (50,75 and 100 cm) on anjan grass (Cellchrus cilillris Linn.) intereropped with Caribbean stylo (Stylosamhes hamata (L.) Taub.) under three levels of phosphorus (0, 30 and 60 kg P2O5/ha) were carried out on sandy clay loam soil to know the suitable spacing of anjan grass for intercropping with legume to get the higher production. Forage production, crude protein yield and metabolisable energy were not affected by row spacing. Application of phosphorus upto 30 kg P2O5/ha gave significantly higher dry matter and crude protein yield as well as metabolisable energy.